Especialidade médica: escolhas e influências - SOUSA, Ivy Quirino de (2016)
An awareness of the factors that influence medical students when choosing their specializations is key to understanding how future doctors choose their specializations. Our aim was to identify which specializations were the most popular among students at the University Center of the State of Pará Faculty of Medicine (Cesupa) and the factors that determined this choice. We carried out a cross-sectional, descriptive and analytical study through the application of questionnaires to first- fourth- and sixth-year students between November 2012 and March 2013. Most students were male (59.2%), with an average age of 22 ± 2 years and a household income of more than 10 minimum monthly wages and at least one relative who is a doctor. The main specializations chosen were: plastic surgery (10.4%), endocrinology (15.7%), and ophthalmology (14.0%) in the first, fourth and sixth years, respectively. The main factor influencing this choice in the first year was parental influence (17.2%) and in the fourth and sixth years, finance (15.8% and 22.8%, respectively). Many factors influence the choice of specializations, and it is necessary to seek ways of attracting students to more general areas.